Rubber particle cavitation in toughened Poly(methyl methacrylate) - Rizzieri, Rosalba (Cranfield University, 2001)
Theoretical and experimental investigations were performed on multiphase polymers; especially rubber toughened (RT) poly(methyl methacrylate) (PMMA) to explore cavitation in the rubbery phase. The main objectives of this project: i. To identify experimental methods to effectively detect rubber particle cavitation. ii. To relate intrinsic toughness with rubber properties (e.g. rubber type, particle morphology, rubber content, particle size). iii. To study the relationships between different pre-treatments, and control the onset of cavitation. Thermal contraction measurements, dynamic mechanical analysis, creep and fracture tests were the techniques adopted. Results from those different methods were examined, compared, and related to a specifically devised mathematical model. They were found consistent. Thermal contraction measurement presents valuable information about the progress of cavitation after pre-strain. It shows extensive rubber cavitation at low longitudinal strain (about 2 - 3%), which is sufficient to produce permanent damage, not recoverable by annealing. Dynamic mechanical procedure estimates the resistance of the soft phase to cavitation in response to mechanically and thermally generated stresses. It can be used to detect distributions of stress and strain within the soft phase after cavitation. The dynamic mechanical tests, supported by electron microscopy, provide further insight into the cavitation mechanism. It is suggested that a complete failure of the rubber will allow any internal stresses to relax, and the rubber glass transition temperature (Tg) to become independent of the tensile stress on the specimen. If the particles remain intact, the loss peak will shift to lower temperature with increasing triaxial tension as the rubber free volume increases in response to a growing dilatational volume strain. To any inbetween state, regarding rubber phase partial failure, will correspond a loss peak in the temperature range defined by Tg of the stretched rubber and the one of the relaxed rubber (upper limit). A major advantage is that thermal contraction measurements and dynamic mechanical tests provide an observation method for the onset of cavitation as a separate process, without the complications that arise when shear yielding or multiple crazing occur at the same time. Analysis based on the energy-balance model suggested multiple cavitation as a possible mechanism for complex particle morphology (e.g. salami or hard-soft-hard core-shell). These results are consistent with experimental data.